(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to analyze the impact of information technology on achieving competitive advantage at North Africa Bank – Tripoli. Information technology was treated as the independent variable, while competitive advantage was the dependent variable. The study used a simple random sample with a target size of 87 respondents. Data were collected through a questionnaire, and after excluding two incomplete forms, 85 valid responses were statistically analyzed using the Statistical Package for the Social Sciences (SPSS). Following the descriptive-analytical approach, the study found a statistically significant impact of information technology on competitive advantage. The main recommendation is to develop a periodic replacement plan for hardware (computers, printers, scanners, and cash-counting machines) whenever technological advancements occur, focusing on AI- and machine-learning-supported devices and expanding their use to new branches and mobile services